Faktor-Faktor yang Memengaruhi Kepuasan Pelanggan Hewan Kurban di Kelurahan Meruyung, Kota Depok - Ismiaji, Bara; Azizah, Siti (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2024)
To be successful in the competitive market for sacrificial animals, with its short selling season and numerous sellers, prioritizing customer satisfaction is essential. This study was conducted in Meruyung Village, Limo District, Depok City on June 24–July 3, 2023, using descriptive-quantitative method to discover the service quality, product quality, and price offered by sellers, and how these three factors affect customer satisfaction of sacrificial animals. Convenience sampling was used to determine the respondents, which is by meeting people at the sales stalls who have bought goats or sheep as sacrificial animals at least once in Meruyung Village. This study involved 70 respondents. Data was obtained using a Likert scale questionnaire via Google Form and processed using multiple regression analysis. The results shows that the quality of service and product, as well as the price factor offered by sacrificial animal sellers, together affect customer satisfaction with sacrificial animals in Meruyung Village, Limo District, Depok City by 36.5%, but only the factor of product quality has a partially significant influence. Therefore, sellers must ensure product quality that meets the requirements of sacrificial animals and customer preferences, as this significantly affects satisfaction.